Production of Salt Tolerance Dwarf Napier Grass (Pennisetum purpureum cv. Mott) Using Tissue Culture and Gamma Irradiation - Pradit Pongtongkam; Surin Peyachoknagul; Jantakarn Arananant; Amara Thongpan; Sayan Tudsri (Agriculture and Natural Resources, 2006)
As high as 95% of callus was induced when young leaves of dwarf Napier grass were cultured in MS medium supplemented with 5% coconut water and 2 mg/l 2,4-D. These calli were of highly compact type. Upon transferring these calli to grow on the plantlet induction medium, it was found that the MS medium containing 5% coconut water, 1 mg/l NAA, 0.5 mg/l BAP and 0.5 mg/l 2,4-D gave the best average plantlet production of 58.8%. Irradiated calli at the levels of 0, 10, 20, 30, 40 and 50 Gy were subject to culturing growth on the selected plantlet induction medium containing different NaCl concentrations of 0, 0.5, 1.0, 1.5 and 2.0%. The total of 108 clones could survive in the salt supplemented medium. These surviving clones were then transferred to grow in the field at National Corn and Sorghum Research Center, Nakorn Rachasima province. Twenty-one of good characteristic clones were selected from the field to be further grown at high salinity soil in Borabue district, Maha Sarakarm province and 8 clones were finally chosen as salt tolerance. DNA fingerprinting patterns of the 21 selected clones were analyzed using AFLP technique with 11 pairs of primers. The patterns were significantly different at high percentage of polymorphism (94.75%). The similarity index among these samples ranged from 0.569 to 0.784 indicating that the morphological difference among them was the result of true mutation induced by irradiation and tissue culturing.